A Customized Python Code for Laser Induced Breakdown Spectroscopy Data Analysis - liew, edwin; Dr. Syed Zuhaib Haider Rizvi (Enhanced Knowledge in Sciences and Technology, 2023)
Laser-induced breakdown spectroscopy (LIBS) is a powerful atomic emission spectroscopic technique for studying the elemental composition of a material. The major spectral analyses include the estimation of self-absorption and calculation of plasma parameters, i.e., electron density and plasma temperature. Popular software packages which are used for LIBS spectral analysis are MATLAB and OriginLab. Getting subscription or purchasing license spectral analysis software is awfully expensive for students and individuals. It motivated this project to write codes for common and spectroscopic analysis of significant importance in Python and make it available for free on GitHub. All coding routines are implemented in Python programming language using Jupyter Notebook as IDE for Python. Coding sections for plotting of LIBS spectra, estimation of self-absorption, calculation of electron density by Stark Broadening method and plasma temperature by Boltzmann Plot method are developed. The output results in Jupyter Notebook are compared with the results obtained from OriginLab software for same calculations. Python is an enormously powerful tool in data analytics with a range of libraries. It is distributed under open-source license and approved by the Open-Source Initiative (OSI). The coding has been uploaded on GitHub and hence available for free to be accessed and used by other researchers.